(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study assessed the factors that may affect the enrollment procedure at Bestlink College of the Philippines in Quezon City. Due to unexpected circumstances, the college had to adopt remote or online enrollment, necessitating adjustments to enrollment procedures. As a result, there were several factors that needed to be considered in order to achieve efficiency. The study found that the respondents strongly agreed that several factors affected the enrollment procedure. The researchers hypothesized that the demographic profile of respondents directly affected the enrollment procedure at Bestlink College of the Philippines. The findings of the study showed that the registrar department was being affected by the internet connection, digital literacy, and delegation management in various ways, especially in the enrollment procedure. The researchers concluded that there was a need for a better and smoother enrollment procedure to be put in place, as both the researchers and the record officers desired. This research revealed that the enrollment procedure needs to be improved or enhanced in order to overcome the future issues that it may face. Remote enrollment and walk-in enrollment should be stable to prevent confusion among those who used it. For remote enrollment, it only takes one website for a student to enroll, check balance, grant modules, etc. To avoid confusion and account loss due to a lot of passwords and accounts to remember. In addition, the budget for a second network provider should be taken into account by the college administration in order to cover the registrar department’s network loss during the enrollment season. Overall, the study demonstrated the importance of assessing factors that may affect enrollment procedures in an educational institution, particularly during unexpected changes.